Asbestos lung burden and asbestosis after occupational and environmental exposure in an asbestos cement manufacturing area: a necropsy study. Issue 12 (December 1998) - Magnani, C; Mollo, F; Paoletti, L; Bellis, D; Bernardi, P; Betta, P; Botta, M; Falchi, M; Ivaldi, C; Pavesi, M
Abstract : OBJECTIVE: The largest Italian asbestos cement factory had been active in Casale Monferrato until 1986: in previous studies a substantial increase in the incidence of pleural mesothelioma was found among residents without occupational exposure to asbestos. To estimate exposure to asbestos in the population, this study evaluated the presence of histological asbestosis and the lung burden of asbestos fibres (AFs) and asbestos bodies (ABs). METHODS: The study comprises the consecutive series of necropsies performed at the Hospital of Casale Monferrato between 1985 and 1988. A sample of lung parenchima was collected and stored for 48 out of 55 necropsies. The AF concentration was measured with a TEM electron microscope with x ray mineralogical analysis. The ABs were counted and fibrosis evaluated by optical microscopy. The nearest relative of each subject was interviewed on occupational and residential history. Mineralogical and histological analyses and interviews were conducted in 1993-4. RESULTS: Statistical analyses included 41 subjects with AF, AB count, and interview. Subjects without occupational exposure who ever lived in Casale Monferrato had an average concentration of 1500 AB/g dried weight (gdw); Seven of 18 presented with asbestosis or small airway lung disease (SAL). G2 asbestosis was diagnosed in two women with no occupational asbestos exposure. One of them had been teaching at a school close to the factory for 12 years. Ten subjects had experienced occupational asbestos exposure, seven in asbestos cement production: mean concentrations were 1.032 x 10(6) AF/gdw and 96, 280 AB/gdw. Eight of the 10 had asbestosis or SAL. CONCLUSION: The high concentration of ABs and the new finding of environmental asbestosis confirm that high asbestos concentration was common in the proximity of the factory. Subjects not occupationally exposed and ever living in Casale Monferrato tended to have higher AB concentration than subjects never living in the town (difference not significant). The concentrations of ABs and AFs were higher than those found in other studies on nonoccupationally exposed subjects.